Letter - Stolz, George
042-0125-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE : President: W.M. Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W Schevenels TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 45-88 AFFILIATED COUNTRIES : ARGENTINE BELGIUM CANADA CHINA CZECHOSLOVAKIA DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN HOLLAND HUNGARY INDIA LUXEMBURG MEXICO NEW ZEALAND NORWAY PALESTINE POLAND RUMANIA SPAIN SWEDEN SWITZERLAND UNITED STATES YUGOSLAVIA St/G. Letter No. 4th August, 1937, Comrade W.M. Citrine, Trades Union Congress General Council Transport House Smith Square London S.W.1. Dear Comrade Citrine, With reference to your letter of 3rd August in which you are urging the photograph of the plate indicating that it was a memorial to the late Ray Cox, I have to inform you that I have already asked comrade August de Block, who is making all these arrangements, for such a photograph, but that I have not got an answer yet. As Comrade Schevenels is in Spain at the moment I have written to him asking him to get the photo on the spot. I hope that you will this time get what you are asking for. Yours fraternally, G. Stolz, Assistant Secretary. 292/946/42/125